Pengaruh Perspektif Tarif Berobat, Fasilitas Kesehatan Dan Standar Pelayanan Terhadap Kepuasan Pasien Rawat Jalan Di RSUD. Gambiran Kediri Kota Kediri - Farra Kharisma Rinta (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Study aims to determine the effect between the variables perspective of treatment rates (X1) health facilities (X2) and service standards (X3) on patient satisfaction (Y) at Gambiran Hospital, Kediri City. Type of research. This is quantitative research. The data collection techniques used are primary data and secondary data. Sample selection using purposive sampling method, the number of samples in the study obtained as many as 91 respondents at Gambiran Hospital, Kediri City. This research data was obtained through questionnaires, interviews, and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classic Assumption Test, Multiple linear regression analysis, t test, Classical Assumption Test, Multiple linear regression analysis, Classical Assumption Test Classical Assumption Test, Multiple linear regression analysis, Test t, Test F and Test the coefficient of determination. Determination. From the results conducted in the study, it shows that the variables perspective of treatment rates, health facilities and service standards on patient satisfaction. patient satisfaction at Gambiran Hospital, Kediri City. The results of the study obtained a multiple linear regression equation Y = 11.078 + 0.233X1 + 0.426X2 + 0.718X3 and the results of the t test of the perspective variable of treatment rates partially significant effect on patient satisfaction. Health facilities partially significant effect on patient satisfaction. Service Standards partially significant effect on patient satisfaction. F test results obtained Fcount results with a significance value of 0.000 <0.05. From the results of the analysis it can be concluded that the perspective of treatment rates, health facilities and service standards simultaneously and significantly affect patient satisfaction at Gambiran Hospital, Kediri City.